2017
DOI: 10.1109/tnse.2016.2627502
|View full text |Cite
|
Sign up to set email alerts
|

Confidence Sets for the Source of a Diffusion in Regular Trees

Abstract: We study the problem of identifying the source of a diffusion spreading over a regular tree. When the degree of each node is at least three, we show that it is possible to construct confidence sets for the diffusion source with size independent of the number of infected nodes. Our estimators are motivated by analogous results in the literature concerning identification of the root node in preferential attachment and uniform attachment trees. At the core of our proofs is a probabilistic analysis of Pólya urns c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 24 publications
1
67
0
Order By: Relevance
“…It would be interesting to study what additional constraints could ensure the agreement of both persistent nodes. Our results show that the top K central nodes obtained according to the centrality measure ψ stabilizes after a finite number of steps. The results in and showed that confidence sets for the root node may be constructed by selecting the most central nodes according to ψ. However, the set so obtained may be suboptimal in terms of the size required as a function of the error probability ϵ .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be interesting to study what additional constraints could ensure the agreement of both persistent nodes. Our results show that the top K central nodes obtained according to the centrality measure ψ stabilizes after a finite number of steps. The results in and showed that confidence sets for the root node may be constructed by selecting the most central nodes according to ψ. However, the set so obtained may be suboptimal in terms of the size required as a function of the error probability ϵ .…”
Section: Discussionmentioning
confidence: 99%
“…The results in and showed that confidence sets for the root node may be constructed by selecting the most central nodes according to ψ. However, the set so obtained may be suboptimal in terms of the size required as a function of the error probability ϵ . It would be interesting to see whether other centrality measures such as those corresponding to the maximum likelihood estimator are also “robust” in the sense that they produce a stable output after some finite time. The problem of establishing persistence of centrality in non‐trees (eg, in preferential or uniform attachment models where more than one node is added at each step) appears to be very challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…infection paths, inside the infected subgraph. Their linear time algorithm is an optimal estimator in regular trees and enjoys strong theoretical properties in such idealized settings [34]. Zhou and Ying [26] consider SIR dynamics on a tree and show that the most likely infection path is rooted at a Jordan center (JC) of the infected set O, that is, a node with minimum eccentricity (i.e., maximum distance to others).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou and Ying [26] consider SIR dynamics on a tree and show that the most likely infection path is rooted at a Jordan center (JC) of the infected set O, that is, a node with minimum eccentricity (i.e., maximum distance to others). It has been shown [26,34] that in regular trees, eccentricity ranking generates, with high probability, a confidence set containing the true source, whose size does not grow with the infection size.…”
Section: Introductionmentioning
confidence: 99%